2022
DOI: 10.1186/s13052-022-01277-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic therapeutic care pathway for pediatric food allergies and intolerances in Italy: a joint position paper by the Italian Society for Pediatric Gastroenterology Hepatology and Nutrition (SIGENP) and the Italian Society for Pediatric Allergy and Immunology (SIAIP)

Abstract: Epidemiologic data suggest an increased prevalence of pediatric food allergies and intolerances (FAIs) during the last decades. This changing scenario has led to an increase in the overall healthcare costs, due to a growing demand for diagnostic and treatment services. There is the need to establish Evidence-based practices for diagnostic and therapeutic intervention that could  be adopted in the context of public health policies for FAIs are needed.This joint position paper has been prepared by a group of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…As a result, profilins lose their allergenic potency after being cooked (Deng & Yin, 2019;Offermann et al, 2016). Nevertheless, although the cooking process destroys the IgE-binding epitopes present in profilin-containing foods, some cross-reactive T cell activity in vitro can still be observed due to the presence of remaining continuous epitopes (Berni Canani et al, 2022;Poncet et al, 2020). Song et al (2008) expressed a pan-allergen profilin from mango (M. indica) using E. coli BL21 DE3 system and explored its immunoreactivity with mango allergic patients sera.…”
Section: Man Imentioning
confidence: 99%
“…As a result, profilins lose their allergenic potency after being cooked (Deng & Yin, 2019;Offermann et al, 2016). Nevertheless, although the cooking process destroys the IgE-binding epitopes present in profilin-containing foods, some cross-reactive T cell activity in vitro can still be observed due to the presence of remaining continuous epitopes (Berni Canani et al, 2022;Poncet et al, 2020). Song et al (2008) expressed a pan-allergen profilin from mango (M. indica) using E. coli BL21 DE3 system and explored its immunoreactivity with mango allergic patients sera.…”
Section: Man Imentioning
confidence: 99%
“…154 The basophil activation test is a patient-friendly, in vitro alternative that can provide a definitive diagnosis without the need for an oral challenge. 154 Similarly, the mast cell activation test can support a diagnosis of plant food allergy. 155 Although biomarkers for food allergy are lacking, transcriptomic, epigenomic, microbiomic, and metabolomic biomarkers are being investigated.…”
Section: Food Allergymentioning
confidence: 99%
“…2 When breastfeeding is not possible, there are a variety of special formulas for infants and children with CMPA that can be selected based on the patient's age, disease features, and local availability. [2][3][4][5] It has been suggested that compared with breastfeeding, formula feeding is more likely to cause malnutrition in children with CMPA. 6,7 Formulas for the dietary management of paediatric CMPA contain different protein sources.…”
mentioning
confidence: 99%
“…1 Management of CMPA includes elimination of cow's milk proteins from the diet and identification of suitable alternatives for a nutritionally balanced diet. 2 When breastfeeding is not possible, there are a variety of special formulas for infants and children with CMPA that can be selected based on the patient's age, disease features, and local availability. [2][3][4][5] It has been suggested that compared with breastfeeding, formula feeding is more likely to cause malnutrition in children with CMPA.…”
mentioning
confidence: 99%